2021
DOI: 10.1155/2021/6616693
|View full text |Cite
|
Sign up to set email alerts
|

The Antiobesity Effect of GLP-1 Receptor Agonists Alone or in Combination with Metformin in Overweight /Obese Women with Polycystic Ovary Syndrome: A Systematic Review and Meta-Analysis

Abstract: Objectives. Both glucagon-like peptide-1 receptor agonists (GLP-1RAs) and metformin (MET) have markedly antiobesity effects in overweight/obese polycystic ovary syndrome (PCOS) patients. However, there was no literature to compare the antiobesity effects of these two medicines. Therefore, a systematic review and meta-analysis were conducted in our present study to evaluate the antiobesity effects of GLP-1RAs either as monotherapy or combined with MET in comparison with MET alone in overweight/obese PCOS patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 42 publications
0
11
0
2
Order By: Relevance
“…Previous narrative reviews supporting the use of GLP-1 RAs in PCOS focused on single-center RCT and observational studies. 49 Two meta-analyses of GLP-1 RAs versus metformin in PCOS included six and eight RCT studies, respectively, 50,51 which concluded GLP-1 RAs were beneficial with or without metformin for metabolic, reproductive, and anthropometric parameters. However, these analyses combined exenatide and liraglutide in varying protocols and dosing regimens.…”
Section: Discussionmentioning
confidence: 99%
“…Previous narrative reviews supporting the use of GLP-1 RAs in PCOS focused on single-center RCT and observational studies. 49 Two meta-analyses of GLP-1 RAs versus metformin in PCOS included six and eight RCT studies, respectively, 50,51 which concluded GLP-1 RAs were beneficial with or without metformin for metabolic, reproductive, and anthropometric parameters. However, these analyses combined exenatide and liraglutide in varying protocols and dosing regimens.…”
Section: Discussionmentioning
confidence: 99%
“…The following year, another meta-analysis published results focusing on the weight loss effect of GLP-1RAs individually or combined with metformin in overweight/obese women with PCOS. It showed that GLP-1RAs were associated with a more significant effect compared with metformin-only treatment in eight eligible RCTs [ 55 ].…”
Section: Comparison Of Glp-1 Receptor Agonists To Metformin and The P...mentioning
confidence: 99%
“…[122]. By changing the dopaminergic and Women with PCOS, who have overweight or obesity (n = 84) 84 LIRA 1.2 mg alone (n = 21), MET 1000 mg BID + LIRA 1.2 mg combination arm (n = 22), (12-week follow-up) 87 Women with obesity and PCOS (n = 43) 87…”
Section: Clinical Datamentioning
confidence: 99%
“…LIRA 1.2 mg was found to be more effective in decreasing BW than MET in subjects with severe obesity and PCOS [ 86 ]. GLP-1 RAs alone or combined with MET compared to MET alone had a better effect in terms of BMI and WC reduction in PCOS patients with overweight and obesity [ 87 ].…”
Section: Polycystic Ovary Syndromementioning
confidence: 99%